2011
DOI: 10.1186/1471-2180-11-77
|View full text |Cite
|
Sign up to set email alerts
|

Novel molecular markers of Chlamydia pecorum genetic diversity in the koala (Phascolarctos cinereus)

Abstract: BackgroundChlamydia pecorum is an obligate intracellular bacterium and the causative agent of reproductive and ocular disease in several animal hosts including koalas, sheep, cattle and goats. C. pecorum strains detected in koalas are genetically diverse, raising interesting questions about the origin and transmission of this species within koala hosts. While the ompA gene remains the most widely-used target in C. pecorum typing studies, it is generally recognised that surface protein encoding genes are not su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 68 publications
(100 reference statements)
2
47
5
Order By: Relevance
“…Using novel molecular markers (tarP in addition to open reading frame 663 [ORF663], incA, and ompA), the findings of Marsh et al (24) strengthened previous observations that koala C. pecorum strains are genetically diverse (22). In contrast to the previous study, however, the latter study showed that koala C. pecorum strains were phylogenetically distinct from C. pecorum livestock strains (24), although the study was limited by a lack of Australian livestock samples. Use of these polymorphic genes in a previous study, alone or in addition to housekeeping genes as targets of a multivirulence locus-typing scheme (MVLST), allowed for the discrimination of C. pecorum strains from livestock that were isolated from diseased and healthy animals (25).…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Using novel molecular markers (tarP in addition to open reading frame 663 [ORF663], incA, and ompA), the findings of Marsh et al (24) strengthened previous observations that koala C. pecorum strains are genetically diverse (22). In contrast to the previous study, however, the latter study showed that koala C. pecorum strains were phylogenetically distinct from C. pecorum livestock strains (24), although the study was limited by a lack of Australian livestock samples. Use of these polymorphic genes in a previous study, alone or in addition to housekeeping genes as targets of a multivirulence locus-typing scheme (MVLST), allowed for the discrimination of C. pecorum strains from livestock that were isolated from diseased and healthy animals (25).…”
contrasting
confidence: 54%
“…The complete list of isolates from the sequences included for analysis are described in Table S1 in the supplemental material. Five koala isolates from wild koala populations in southeast Queensland (SEQLD), Australia, were previously isolated and described by Marsh and colleagues (24). HK gene fragment sequences for three koala C. pecorum isolates from SEQLD and the sheep C. pecorum polyarthritis type strain IPA were extracted from their draft genomes (A. Polkinghorne, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Recent research also suggests ompA is a valuable epidemiological marker for phylogenetic analysis (Marsh et al, 2011), although it may overestimate whole-genome evolution due to its exposure to strong selection pressure and recombination (Harris et al, 2012). Here, we used ompA genotyping to reveal that, in comparison with the considerable heterogeneity seen in northern koala populations (Kollipara et al, 2013), C. pecorum ompA genotype B dominates in samples collected from Victorian koalas.…”
Section: Discussionmentioning
confidence: 99%
“…C. pecorum in livestock species such as cattle, pigs, sheep and goats have also been genotyped using ompA (Jackson et al, 1997;Mohamad et al, 2014). Although a number of different methods are now available to genotype C. pecorum samples (Marsh et al, 2011;Jelocnik et al, 2013), the existing catalogue of ompA sequences from northern koala populations makes it a useful tool to undertake comparisons with Victorian koala populations. Interestingly, differences in the presence of a chlamydial plasmid, a known virulence factor in some chlamydial species (O'Connell et al, 2007), was also found to be a distinguishing feature of C. pecorum strains from northern populations compared with those from southern populations in South Australia (Jelocnik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Veterinarians from agriculturally productive areas throughout Australia regularly report cases of chlamydiosis in sheep and cattle 8,9 , but the information about the genetic diversity of strains infecting livestock is lacking. A range of previous molecular studies suggested that C. pecorum strains infecting koala are genetically diverse 10,11 ; however, none of the studies investigated how and whether these strains are related to livestock strains. It has been hypothesised that the origin of koala C. pecorum infections is associated with the import of 'presumably C. pecorum infected' livestock in the late 1780s 3 .…”
Section: The Curious Case Of Chlamydia Pecorum Infections In Australiamentioning
confidence: 99%